Aksi Simpatik Edukasi Bahaya Merokok melalui Media Interaktif pada Masyarakat di Car Free Day Taman Blambangan Banyuwangi - Masroni; Desi Trianita (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Sympathetic Action for Smoking Hazard Education through Interactive Media among the Community at Taman Blambangan Car Free Day, Banyuwangi. Tobacco use remains a preventable public health problem, while secondhand smoke continues to expose non-smokers in homes and public spaces. This community service activity aimed to strengthen public understanding of smoking hazards, smoking-related diseases, secondhand-smoke risks, and supportive behavior toward smoke-free environments. The activity was conducted on 1 June 2025 from 05:30 to 10:00 WIB at the Taman Blambangan Car Free Day, Banyuwangi. The target group was the general public attending the event. Implementation combined direct and peer-oriented health education, interactive questions and answers, and visual printed media, including banners, posters, leaflets, and warning stickers. The program followed preparation, implementation, monitoring, and evaluation stages. The documented attendance sheet contained 18 signed participants for the focused education session, while educational interaction also reached other Car Free Day visitors. The activity report categorized the program as successful and recorded the delivery of educational messages and smoking-hazard stickers as concrete outputs. Because numerical pre-test and post-test scores were not retained in the report, changes in knowledge are interpreted qualitatively from monitoring, participant responses, and completion of planned outputs. Periodic education using standardized pre-post instruments is recommended to strengthen outcome measurement and program sustainability.